Digital Literacy and Growth Mindset to Predict Technology Acceptance During Learning Processes - Vincent Suryawidjaja (Psikodimensia: Kajian Ilmiah Psikologi, 2023)
Covid-19 pandemic had impacted the urgency of using digital learning technology. Literature studies showed that teachers needed Digital Literacy and Growth Mindset to accept the new technology used. This study examined the contribution of the Digital Literacy and Growth Mindset in predicting the usage of Learning Management Systems (LMS). Respondents of this study were 60 lecturers in one university in Jakarta, where the LMS has been developed to be used in their learning and teaching processes. They were consented to become subjects of the study. Data were collected using questionnaire and analyzed by multiple regression. Results of this study indicated that Digital Literacy and Growth Mindset simultaneously had a significant contribution to the effective usage of LMS (R2=0.419, F (2) = 20.545, p0.05). This research also showed that Digital Literacy had contributed more than the Growth Mindset (β=0.406 β=0.295). In facing the digital learning transformation during the pandemic time, collaboration is needed from all important actors in the education sector, such as lecturers, universities, and students, to support the development of a better digital learning ecosystem. It is suggested to upscale the study to generate the hypothesis that Digital Literacy is truly a critical aspect to be studied in this digital learning technology acceleration era.